Cell-specific bioorthogonal tagging of glycoproteins - Anna Cioce; Beatriz Calle; Tatiana Rizou; Sarah C. Lowery; Victoria L. Bridgeman; Keira E. Mahoney; Andrea Marchesi; Ganka Bineva-Todd; Helen Flynn; Zhen Li; Omur Y. Tastan; Chloe Roustan; et al. (Nature Communications, 2022)
Changes in glycoprotein expression are correlates of disease, but secreted glycoproteins cannot be accurately traced to their cell line of origin. Here, the authors develop a strategy to chemically tag and profile glycoproteins in a cell line-specific manner in co-culture systems and in vivo.